Measuring link bandwidths using a deterministic model of packet delay. - Lai, Kevin (Computer communication review.)
We describe a deterministic model of packet delay and use it to derive both the packet pair [2] property of FIFO-queueing networks and a new technique packet tailgating) for actively measuring link bandwidths. Compared to previously known techniques, packet tailgating usually consumes less network bandwidth, does not rely on consistent behavior of routers handling ICMP packets, and does not rely on timely delivery of acknowledgments.